Synthesis and optical properties of ZnAl2O4/Al2O3:Cr3+ composite materials - Loan, Trinh Thi (VNU Journal of Science: Mathematics - Physics; Vol 34 No 1, 2018)
Zinc aluminate - alumina (ZnAl 2 O 4 /Al 2 O 3 ) systems doped with Cr 3+ different concentrations were synthesized by sol-gel method. The samples were characterized by X-ray diffraction (XRD), photoluminescence (PL) and photoluminescence excitation (PLE) spectra. The results showed that Cr 3+ dopant concentration had a significant effect on the lattice constants of ZnAl 2 O 4 /Al 2 O 3 composite and their luminescence characteristics.